2019
DOI: 10.1007/s00204-019-02410-z
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary and pleural toxicity of potassium octatitanate fibers, rutile titanium dioxide nanoparticles, and MWCNT-7 in male Fischer 344 rats

Abstract: Potassium octatitanate (K 2 O•8TiO 2 , POT) fibers are used as an alternative to asbestos. Their shape and biopersistence suggest that they are possibly carcinogenic. However, inhalation studies have shown that respired POT fibers have little carcinogenic potential. We conducted a short-term study in which we administered POT fibers, and anatase and rutile titanium dioxide nanoparticles (a-nTiO 2 , r-nTiO 2) to rats using intra-tracheal intra-pulmonary spraying (TIPS). We found that similarly to other material… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 25 publications
1
14
0
Order By: Relevance
“…As can be seen in Additional file 1, most of the studies followed the exposed animals for 12–15 months or less, and none of these studies reported development of mesothelioma in the exposed animals. Similarly, in our study, no tumors were observed in the rats sacrificed at 1 year [12]. Only 6 studies followed the exposed animals for 2 years.…”
Section: Discussionsupporting
confidence: 66%
See 4 more Smart Citations
“…As can be seen in Additional file 1, most of the studies followed the exposed animals for 12–15 months or less, and none of these studies reported development of mesothelioma in the exposed animals. Similarly, in our study, no tumors were observed in the rats sacrificed at 1 year [12]. Only 6 studies followed the exposed animals for 2 years.…”
Section: Discussionsupporting
confidence: 66%
“…Both POT and MWCNT-7 fibers were detected in the lungs, trachea, mediastinal lymph nodes, kidney, spleen, liver, and testis (data not shown). In contrast, and unlike the 1-year sacrifice (see Additional file 4: Figure S3 in Abdelgied et al, 2019 [12]), r-nTiO2 particles were not detected in any of these organs. Alveolar macrophage numbers were increased in the POT and MWCNT-7 treated rats (Fig.…”
Section: Resultsmentioning
confidence: 84%
See 3 more Smart Citations